Electromyographic activity of the masseter muscle in individuals with group function and canine guidance - Nathália de Oliveira Domingos; Roberto Bernardino Júnior; Patrícia Teixeira de Carvalho Gaspar; Frederico Balbino Lizardo; César Ferreira Amorim; Daniela Cristina de Oliveira Silva (Tabriz University of Medical Sciences, 2021)
Background. There is no general consensus in restorative dentistry about which lateral guidance should be established. Some studies have shown that canine guidance decreases the tension of masticatory muscles. Others have reported that group function might achieve a better physiologic distribution of occlusal forces. Also, some reports have shown that both guidances are equally acceptable. Despite all discussions, clinical evidence of one guidance being superior to another is limited. Thus, this study aimed to analyze the electromyographic (EMG) activity of masseter muscles in individuals with group function and canine guidance. Methods. Twenty volunteers of both genders, aged 20-25, were divided into two groups: GF (group function guidance, n=10) and CA (canine guidance, n=10). EMG activity of masseters was captured using surface electrodes during habitual maximum intercuspation (HMI) and right and left lateral jaw movements and recorded using EMG amplitude values (RMS - root means square). Student's t-test was used to compare mean RMS values between the groups and lateral movements in each group. Results. During HMI, there was no difference in masseter EMG activity between the groups. Both masseters showed higher activity in group GF only on the right side during lateral movements, while the left masseter exhibited higher activity on the nonworking side in both groups. The activity of both masseters distributed by tooth was higher in group CA. Conclusion. During tooth restorative procedures, any guidance is acceptable considering HMI. However, group function guidance is more favorable during lateral movements due to greater dissipation of occlusal pressures.